Shaping children's moral development through the Among Ki Hajar Dewantara System at SD Labschool Cibubur - Nurhayati, Siti; Yufiarti; Totok Bintoro (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
This study aims to investigate the impact of the Among Ki Hajar Dewantara System on the moral development of children in SD Labschool Cibubur. The problem at hand is a lack of understanding of the extent to which the Among System affects the moral development of students, as well as the obstacles that may be encountered in its application. The research method used is a case study with a focus on the interaction between the Among System and the moral development of students. The subjects of the study included teachers, students, and parents. Data were collected through interviews, classroom observation, and documentation analysis. The data analysis method used is thematic analysis, where data from various sources are grouped and analyzed based on emerging themes. The results showed that the Among System had a significant positive impact on children's moral development, with improvements in the understanding and application of moral values such as honesty, responsibility, and empathy. The recommendation of this study is that schools and educators consider the integration of Among principles in their curricula to support more holistic moral development in children.